Effect of DIDS Anion Transport Inhibitor on Erythrocyte Resistance to Change in Osmotic and Temperature Medium Parameters - Melikhova, S. V.; Nipot, E. E.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2006)
Erythrocyte sensitivity to posthypertonic lysis (PHL) was established to be dependent on dehydration medium composition, duration of hypertonic incubation and rehydration medium temperature. DIDS anion transport inhibitor causes a manifested protective effect on erythrocytes under PHL conditions when dehydration medium comprises a non-electrolyte. DIDS protective effect is slightly manifested and depends on rehydration medium temperature under dehydration in electrolyte solution. The factor, controlling erythrocyte sensitivity to PHL is assumed to be the rate of volume changes in erythrocytes at both incubation stages.